Influence of Obesity and Type 2 Diabetes on Calcium Handling by Skeletal Muscle: Spotlight on the Sarcoplasmic Reticulum and Mitochondria - Eshima, Hiroaki (Frontiers in Physiology, 2021)
Obesity and diabetes have been shown to interfere with energy metabolism and cause peripheral insulin resistance in skeletal muscle. However, recent studies have focused on the effect metabolic insult has on the loss of muscle size, strength, and physical function. Contractile dysfunction has been linked to impaired intracellular Ca2+ concentration ([Ca2+]i) regulation. In skeletal muscle, [Ca2+]i homeostasis is highly regulated by Ca2+ transport across the sarcolemma/plasma membrane, the golgi apparatus, sarcoplasmic reticulum (SR), and mitochondria. Particularly, the SR and or mitochondria play an important role in the fine tuning of this metabolic process. Recent studies showed that obesity and insulin resistance are associated with interactions between the SR and mitochondrial networks (the dynamic tubular reticulum formed by mitochondria), suggesting that metabolic disorders alter Ca2+ handling by these organelles. These interactions are facilitated by specific membrane proteins, including ion channels. This review considers the impact of metabolic disorders, such as obesity and type 2 diabetes, on the regulation of [Ca2+]i in skeletal muscle. It also discusses the mechanisms by which this occurs, focusing chiefly on the SR and mitochondria networks. A deeper understanding of the effect of metabolic disorders on calcium handling might be useful for therapeutic strategies.